Identification of the educational needs and feasible educational modalities for specialist nurses working with ophthalmic patients in a tertiary eye centre in Singapore. (December 2016) - Aw, Ai Tee; Drury, Vicki
Aims: We aim to identify the educational needs and feasible educational modalities for specialist nurses working with ophthalmic patients in a tertiary eye centre in Singapore. Design: This was a mixed-method study utilising paper-based surveys and focus groups with nurses working at a tertiary eye centre in Singapore. Participants: One hundred nurses were invited to respond to the survey, with a response rate of 91%. Two focus groups with a total of 19 nurses were facilitated. Methods: Participants completed a modified Hennessy–Hicks survey. Among these participants 19 were invited to participate in a focus group. Descriptive statistical analysis was performed on the survey results. Focus groups were analysed using the inductive thematic analysis procedure described by Braun and Clarke. Findings: The participants in this study reported a need for ophthalmic-specific education programmes, more training in patient education and a need to broaden clinical exposure and experience. Conclusion: For ophthalmic nursing, where the workforce and patient population are considered relatively small, and postgraduate programmes are limited, the need to develop local education strategies to meet workforce needs has emerged.